2010
DOI: 10.1258/jrsm.2009.090299
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary metastasectomy in colorectal cancer: a systematic review and quantitative synthesis

Abstract: SummaryObjectives Surgical removal of pulmonary metastases from colorectal cancer is undertaken increasingly but the practice is variable. There have been no randomized trials of effectiveness. We needed evidence from a systematic review to plan a randomized controlled trial.Design A formal search for all studies concerning the practice of pulmonary metastasectomy was undertaken including all published articles using pre-specified keywords. Abstracts were screened, reviewed and data extracted by at least two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
98
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(107 citation statements)
references
References 59 publications
(67 reference statements)
4
98
0
5
Order By: Relevance
“…Similar to the case of liver metastasis from rectal cancers, complete resection of metastatic lung nodules also significantly improves long-term survival (13), and it has been reported that the 5-year survival rate of patients suitable for pulmonary metastasectomy is 38.3-63.7% (14). Advances in surgical techniques have resulted in the indication for pulmonary metastasectomy being extended beyond single isolated lung metastases, but the efficacy of this surgery is still unclear (15). As curative resection of pulmonary metastasis has become possible in a greater proportion of patients, preoperative investigations for metastatic staging of colon and rectal cancer are becoming increasingly important.…”
Section: Original Articlementioning
confidence: 94%
“…Similar to the case of liver metastasis from rectal cancers, complete resection of metastatic lung nodules also significantly improves long-term survival (13), and it has been reported that the 5-year survival rate of patients suitable for pulmonary metastasectomy is 38.3-63.7% (14). Advances in surgical techniques have resulted in the indication for pulmonary metastasectomy being extended beyond single isolated lung metastases, but the efficacy of this surgery is still unclear (15). As curative resection of pulmonary metastasis has become possible in a greater proportion of patients, preoperative investigations for metastatic staging of colon and rectal cancer are becoming increasingly important.…”
Section: Original Articlementioning
confidence: 94%
“…(Figure 1) The shortest survival period after surgery was 29 days and the longest -81 months. Although CRC is referred to as a systemic disease and despite doubts about the effect of locoregional therapy in its management, many surgeons perform surgical resection of lung metastases in properly selected patients (19)(20)(21)(22)(23)(24). In general, the presence of metastases portends a poor prognosis; however, according to some studies 5-year survival rate reaches 50% (25).…”
Section: Resultsmentioning
confidence: 99%
“…Some even report 5-year survival rate of 67.2% (27). Currently, although there are studies calling into question the positive effects of surgery in patients with pulmonary metastases from CRC (22), it remains a significant component of the treatment of lung metastatic disease, and its practice is widely accepted worldwide, resulting in low mortality rates and increased five-year survival rates (28)(29)(30). …”
Section: Resultsmentioning
confidence: 99%
“…In 1976, the study made by Herrer, et al had revealed the staging effect of CEA on colon cancer, namely preoperative elevated CEA level suggests the tumor is at an advanced stage (Herrere et al, 1979). Later, a lot of researchers also believed that preoperative CEA level was associated with the tumor range (Yamashita et al, 2009;Fiorentino et al, 2010;Xu et al, 2011). When CEA level > 20 ng/mL, the patients at phase Ducks D accounted for 37%.…”
Section: Discussionmentioning
confidence: 99%